A Longitudinal Study of the Association of Clinical Indices of Cardiovascular Autonomic Function with Breast Cancer Treatment and Exercise Training. (26th September 2018) - Kirkham, Amy A.; Lloyd, Matthew G.; Claydon, Victoria E.; Gelmon, Karen A.; McKenzie, Donald C.; Campbell, Kristin L.
Abstract: Background: Cardiovascular autonomic dysfunction is an early marker for cardiovascular disease. Anthracycline chemotherapy and left‐sided radiation for breast cancer are associated with negative autonomic function changes. This study's objectives were to characterize changes in, and the association of exercise training with, clinical indices of cardiovascular autonomic function across the trajectory of breast cancer therapy. Subjects, Materials, and Methods: Seventy‐three patients receiving adjuvant chemotherapy participated to varying degrees in supervised aerobic and resistance exercise during chemotherapy ± radiation and for 20 weeks after. Resting heart rate (HRrest ) and blood pressure were measured weekly during chemotherapy. HRrest, exercise heart rate recovery (HRrecovery ), and aerobic fitness were measured at enrollment, end of chemotherapy ± radiation, and 10 and 20 weeks after treatment. Results: During chemotherapy, HRrest increased in a parabolic manner within a single treatment and with increasing treatment dose, whereas systolic and diastolic blood pressure decreased linearly across treatments. Tachycardia and hypotension were present in 32%–51% of participants. Factors associated with weekly changes during chemotherapy included receiving anthracyclines or trastuzumab, days since last treatment, hematocrit, and exercise attendance. Receipt of anthracyclines, trastuzumab, and left‐sided radiation individually predicted impairments of HRrest and HRrecovery during chemotherapy ± radiation; however, aerobic fitness change and at least twice‐weekly exercise attendance predicted improvement. By 10 weeks after treatment, HRrest and blood pressure were not different from prechemotherapy. Conclusion: In this study, chemotherapy resulted in increased HRrest and tachycardia, as well as decreased blood pressure and hypotension. Anthracyclines, trastuzumab, and left‐sided radiation were associated with HRrest elevations and impairments of HRrecovery, but exercise training at least twice a week appeared to mitigate these changes. Implications for Practice: This study characterized changes in clinically accessible measures with well‐established prognostic value for cardiovascular disease, and investigated associations with cardiotoxic treatments and the positive influence of exercise. The chemotherapy‐related incremental increase in resting heart rate, with tachycardia occurring in one third of patients, and decrease in blood pressure, with hypotension occurring in one half of the patients, is relevant to oncology practitioners for clinical examination or patient report of related symptoms (i.e., dizziness). The weekly dose of two 60‐minute sessions of moderate‐intensity aerobic and resistance exercise that was identified as protective of cardiovascular autonomic impairments can easily be prescribed to patients by oncologists. Abstract : Treatment for breast cancer, including chemotherapy and radiation can have cardiovascular side effects. This study's objectives were to characterize changes in, and the association of exercise training with, clinical indices of cardiovascular autonomic function across the trajectory of breast cancer therapy.